Synthesis zeolitic Imidazolate Framework-8 (Zif-8) In Solvothermal: The Effect Comparison of Metal-Ligand - Muhammad Nadjib; Ratna Ediati; Yudi Aris Sulistiyo; Lutfiatun Nadifah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
Synthesis of ZIF-8 (zeolitic Imidazolate Frameworks-8) have been successfully carried out by the reaction of zinc nitrate and 2-methylimidazolate in DMF (N'N-dimethylformamide) solvent at a temperature of 120 °C for 24 hours. Synthesis of ZIF-8 has been conducted five times with variations molar ratio of metal (Zn2+):ligand (MeIM) consecutive 1:1; 1:1.5; 1:2; 1:2.5 and 1:3 to study the influence of metal-ligand ratio of the crystallinity and morphology of ZIF-8 that was produced. The results of characterization by X-ray diffraction, FTIR and SEM show that ZIF-8 is synthesized with a ratio of metal: ligand = 1:2 showed the highest crystallinity and has the most irregular surface morphology with form box. Keywords: ZIF-8, solvotermal, metal/ligand ratio